Praktek Pelaksanaan Kenduri Kematian Dan Tahlilan Menurut Imam Syafi’i Dan Hanafi (Studi Kasus Di Desa Air Hitam Kecamatan Gebang) - Muhammad Saleh, Muhammad Yusuf, Diyan Yusri (Khazanah : Journal of Islamic Studies, 2022)
Identification of the problems found at the research location, namely: 1. The implementation of tahlilan and death feasts was carried out after the maghrib prayer at the funeral home. So that its implementation in the near future is waiting for the Isha prayer. The problem found was that the congregational Isha prayer was missed because the tahlilan and death feast were still ongoing. 2. Some of the people of Air Hitam, Gebang District, do not accept the implementation of tahlilan and death feasts because they are considered as heretical acts, that is, they were never taught by the Messenger of Allah. The formulation of the problem in this study are: 1. How is the practice of tahlilan and death feast applied in Air Hitam Village, Gebang District? 2. How is the legal analysis regarding the implementation of tahlilan and death feast according to the Imam Shafi'i school of thought? 3. Is the implementation of tahlilan and death feast in Air Hitam Village, Gebang District, against Islamic law? 4. What is the law regarding the implementation of tahlilan according to the scholars of the Shafi'i and Shafi'i schools? The conclusions in this study are: The implementation of tahlilan really helps the community in deepening religious knowledge. Through this tahlilan and in general, the people of Air Hitam Village have noble character and good personality, thus creating a prosperous and peaceful life. The tahlilan facilities that have been provided by the people of Air Hitam Village are adequate, such as community houses and some cash and social gathering money which will be used to hold a meal together after the tahlilan event is over, so lectures are also held.